Effects of Exercise on Neural Changes in Inhibitory Control: An ALE Meta-Analysis of fMRI Studies - Wu, Jinlong; Xiao, Wen; Yip, Joanne; Peng, Li; Zheng, Kangyong; Takyi Bentil, Obed; Ren, Zhanbing (Frontiers in Human Neuroscience, 2022)
Abstract It is widely acknowledged that exercise improves inhibitory control; however, the mechanisms behind the cognitive improvement remain unclear. In this study, we analyze the extant literature on the neuronal effects of exercise on inhibitory control functions. We search four online databases (Pubmed, Scopus, PsycINFO, and Web of Science)  for relevant peer-reviewed studies to identify eligible studies published before September 1, 2021. Among the 4090 candidate studies identified, 14 meet the inclusion criteria and the results of a total of 397 participants in these 14 studies are subsequently analyzed. We quantify the neural effects on the entire brain by using GingerALE software and identify ten clusters of exercise-induced neuronal with with either increases/decreases in the superior frontal, temporal, central, middle temporal, parahippocampal gyrus, precuneus, posterior cingulate cortex, cuneus and caudate. We propose that the effect of exercise on the neural activity related to inhibitory control in the extended frontoparietal and default mode networks. These results provide preliminary evidence of the neural effects of exercise on inhibitory control, although additional research is required to definitively link exercise to changes in neuroplasticity with respect to inhibitory control.